Assessment of generation adequacy taking into account the dependence of the European power system on natural gas - Maike Spilger; Dennis Schneider; Christoph Weber (University of Duisburg-Essen, House of Energy Markets & Finance (HEMF), 2023)
Reductions in gas supply following the Russian invasion of Ukraine have affected the security of supply of the European power system along with other stress factors like low availability of French nuclear reactors. Consequently, more sophisticated approaches to investigate generation adequacy and to anticipate risks in security of supply are needed. Especially a thorough assessment of generation adequacy taking into account both the variability of renewable infeed and the availability of thermal power plants based on a probabilistic approach has been missing so far. In this paper, we apply a novel integrative approach to analyze generation adequacy in a case study for Central Western Europe during the winter half year 2022/2023. The approach makes use of a multivariate probabilistic framework built on publicly available data. For assessing generation adequacy, stochastic distributions are fitted to the data and Monte Carlo simulations are performed to identify future threats to generation adequacy. Results show that based on data available at the end of September 2022, generation adequacy (GA) was at risk in several core European countries, yet that the European interconnected power grid contributed to a strong risk reduction.
Keywords: 330; Security of Supply; Generation Adequacy; Probabilistic; Monte Carlo; Energy System Modeling